Bi-Level Decomposition Approach for Coordinated Planning of an Energy Hub With Gas-Electricity Integrated Systems - Ghasemi, Hosein; Aghaei, Jamshid; Gharehpetian, Gevork B.; Shafie-Khah, Miadreza; Catalão, João P. S. (IEEE, 2022)
Integrationof multiple energy systemsand the presence of smart energy hubs have provided increased flexibility and improved efficiency for the system. In this article, a bi-level decomposition approach (BLDA) is presented for coplanning of electricity and gas networks as well as the energy hub in distribution networks. The proposed multistage planning determines the investment candidates with optimum capacity for the components of integrated systems. Due to the complexity and nonlinearity of the models and energy subsystems interactions, the expansion planning problem is a difficult task with many limitations, especially for large-scale systems. To overcome these obstacles, achieve an optimum response and reduce computation time, a mixed integer linear programming model and a new BLDA methodology are developed in this article. Moreover, to evaluate the effectiveness and superiority of the proposed approach, the interactions among the energy systems are simulated in a large-scale distribution system and the results are compared.
Keywords: Active energy system; Benders decomposition (BD); Integrated expansion planning; Multiple energy carriers; fi=Sähkötekniikka|en=Electrical Engineering|